Natural compound Alternol actives multiple endoplasmic reticulum stress-responding pathways contributing to cell death - Liu, Wang; He, Chenchen; Li, Changlin; Ye, Shazhou; Zhao, Jiang; Zhu, Cunle; Wang, Xiangwei; Ma, Qi; Li, Benyi (Frontiers in Pharmacology, 2024)
Background: Alternol is a small molecular compound isolated from the fermentation of a mutant fungus obtained from Taxus brevifolia bark. Our previous studies showed that Alternol treatment induced reactive oxygen species (ROS)-dependent immunogenic cell death. This study conducted a comprehensive investigation to explore the mechanisms involved in Alternol-induced immunogenic cell death. Methods: Prostate cancer PC-3, C4-2, and 22RV1 were used in this study. Alternol interaction with heat shock proteins (HSP) was determined using CETSA assay. Alternol-regulated ER stress proteins were assessed with Western blot assay. Extracellular adenosine triphosphate (ATP) was measured using ATPlite Luminescence Assay System. Results: Our results showed that Alternol interacted with multiple cellular chaperone proteins and increased their expression levels, including endoplasmic reticulum (ER) chaperone hypoxia up-regulated 1 (HYOU1) and heat shock protein 90 alpha family class B member 1 (HSP90AB1), as well as cytosolic chaperone heat shock protein family A member 8 (HSPA8). These data represented a potential cause of unfolded protein response (UPR) after Alternol treatment. Further investigation revealed that Alternol treatment triggered ROS-dependent (ER) stress responses via R-like ER kinase (PERK), inositol-requiring enzyme 1α (IRE1α). The double-stranded RNA-dependent protein kinase (PKR) but not activating transcription factor 6 (ATF6) cascades, leading to ATF-3/ATF-4 activation, C/EBP-homologous protein (CHOP) overexpression, and X-box binding protein XBP1 splicing induction. In addition, inhibition of these ER stress responses cascades blunted Alternol-induced extracellular adenosine triphosphate (ATP) release, one of the classical hallmarks of immunogenic cell death. Conclusion: Taken together, our data demonstrate that Alternol treatment triggered multiple ER stress cascades, leading to immunogenic cell death.